PERAN PEKERJA SOSIAL TERHADAP PEMBERDAYAAN RUMAH TANGGA MISKIN MELALUI KELOMPOK USAHA BERSAMA - Fahmi Fahmi (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2018)
Poverty still occurs in the household space which causes poverty in a large community level. So it needs efforts to be able to tackle the problem of poverty in the household. One of them is by empowering poor household communities through enhancing the activities of Joint Group Enterprises (KUBE) involving social workers. With this empowerment, it is expected that social workers can carry out their functions and roles to supervise and monitor Joint Group Business actors. The method used is the literature study method with a variety of references that are still relevant. Then this paper produces the following discussion. First, what is the factor of poverty in the household, second, what is the most appropriate effort to empower poor household, and third, how the role of social workers in government programs towards Joint Group Enterprises (KUBE), where this program is one of the activities that can be utilized by poor households.